An Experimental Study of the Use of Coconut Oil-based PCM to Reduce the Thermal Load of Air Conditioners as an Effort to Save Energy - Agung Ariwibowo; Muhammad Irsyad; Amrul Amrul (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
The use of air conditioning affects energy consumption. Thermal load is a big factor that affects energy consumption by air conditioners. For this reason, the thermal load of a room needs to be reduced. One strategy to reduce the room's thermal load is the use of phase change materials (PCM). Coconut oil is a PCM that has a freezing temperature in the range of 21.30 – 21.73 oC which will be investigated in this study. The test was carried out with three room models; without PCM, with PCM partition, and PCM partitioned with night air. Each room model carried out 3 variations of air temperature, as well as 4 variations of the heater. The results showed that the use of coconut oil PCM as a room partition can help reduce the room temperature to 2oC below the AC temperature with a decrease in the use of electrical energy reaching 400 Watts. Air conditioner (AC) merupakan alat untuk mengondisikan udara pada sebuah ruangan. Penggunaannya berdampak pada konsumsi energi listrik. Beban termal menjadi faktor besar yang mempengaruhi konsumsi energi oleh AC. Untuk itu beban termal dari sebuah ruangan perlu dikurangi. Salah satu strategi untuk mengurangi beban termal ruangan yaitu penggunaan phase change material (PCM). Minyak kelapa merupakan PCM yang memiliki suhu beku dengan rentang 21,30 – 21,73 oC yang akan diteliti kali ini. Pengujian dilakukan dengan tiga model ruangan yaitu non PCM, berpartisi PCM, dan berpartisi PCM dengan udara malam. Masing-masing model ruangan dilakukan 3 variasi temperatur udara ,serta 4 variasi heater. Hasil penelitian menunjukkan bahwa penggunaan PCM minyak kelapa sebagai partisi ruangan dapat membantu menurunkan temperatur ruangan sampai 2oC dibawah temperatur AC dengan penurunan penggunaan energi listrik mencapai 400 Watt.